Selecting Heat-Tolerant Corals for Proactive Reef Restoration - Caruso, Carlo; Hughes, Kira; Drury, Crawford (Frontiers in Marine Science, 2021)
Coral reef restoration is an attractive tool for the management of degraded reefs; however, conventional restoration approaches will not be effective under climate change. More proactive restoration approaches must integrate future environmental conditions into project design to ensure long-term viability of restored corals during worsening bleaching events. Corals exist along a continuum of stress-tolerant phenotypes that can be leveraged to enhance the thermal resilience of reefs through selective propagation of heat-tolerant colonies. Several strategies for selecting thermally tolerant stock are currently available and range broadly in scalability, cost, reproducibility, and specificity. Different components of the coral holobiont have different utility to practitioners as diagnostics and drivers of long-term phenotypes, so selection strategies can be tailored to the resources and goals of individual projects. There are numerous unknowns and potential trade-offs to consider, but we argue that a focus on thermal tolerance is critical because corals that do not survive bleaching cannot contribute to future reef communities at all. Selective propagation uses extant corals and can be practically incorporated into existing restoration frameworks, putting researchers in a position to perform empirical tests and field trials now while there is still a window to act.